Bio-encapsulation of allergen-derivatives for specific immunotherapy - Schubert, Fabian; Arcalís, Elsa; Kyral, Maximilian; Jeitler, Barbara; Raith, Marianne; Swoboda, Ines; Stoger, Eva (Frontiers in Plant Science, 2025)
Allergen-specific oral immunotherapy is a disease-modifying treatment already established for respiratory allergies and tested for the treatment of several food allergies, with promising clinical and immunological outcomes. However, orally administered allergens must pass through the gastrointestinal tract, where they are exposed to proteolytic digestion. This study describes the design of multi-layered protein bodies (PBs) in Nicotiana benthamiana as a platform for allergen encapsulation, offering potential advantages for oral immunotherapy. By co-expression of three zein variants we generated multi-layered PBs with distinct core and shell structures containing derivatives of the major fish allergen parvalbumin. The specific layering and structural integrity of the PBs were confirmed by confocal microscopy. Correlative light and electron microscopy (CLEM), combined with immunolabelling, was then used to verify the exact position of the allergens in the different layers of the PBs. In vitro experiments simulating the gastrointestinal digestion process revealed a significantly increased, layer-specific resistance of PB-encapsulated allergens compared to soluble allergens. Additionally, the uptake of PBs by human intestinal epithelial cells was simulated using Caco-2 cells. Our work provides further insight into protein storage organelle formation and novel bioencapsulation strategies to produce customized delivery vehicles, whose compartments may offer increased protection against enzymatic degradation and support prolonged persistence upon oral administration.